An introduction of landscape visualisation as a tool to propose the future design of humane open-spaces for employees among tall buildings / Era Nopera Rauzi - Rauzi, Era Nopera (2018)
Tall buildings is one solution for urban areas where limited available land and high prices become a problem for investors. This causes the optimization of land less attention to the social impact of increasing the number of high buildings in city. The fact happens nowday is the unavailability of public open space for micro economic activities such as street vendors who are currently crowded around the edge of the highway surrounding tall buildings. Therefore, this study aims to make the planning of future design of humane open space for workers and office workers. One of the methods used is landscape visualisation to see the existing conditions. the example of selected area is karet pasar baru timur 5 street located between Sahid Sudirman complex and Apartement Pavilion. According to study of one photo captured on road condition, future design planning can be made by reducing the road sections of the road and expanding the sidewalk located in the middle that separates the traffic lane. Thus, the open space is more humane with the arrangement of parking areas and planning good sanitation and feasible course. This result is a draft proposal as the introduction of further research to be conducted with more interdisciplinary knowledge sectors review